PENGARUH MODEL PEMBELAJARAN QUESTION STUDENT HAVE DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD AL HIJRAH KOTA MAKASSAR - Erwin Nurdiansyah (Fakultas Keguruan dan Ilmu Penidikan UIM, 2019)
Abstract: The Effect of Question Student Have Learning Model in Improving Mathematics Learning Outcomes of Students in the Grade V of SD Al Hijrah Makassar. The purpose of this study were: 1) To find out the description of mathematics learning outcomes in fifth grade students of SD Al Hijrah Makassar before applying the Question Student Have learning model. 2) To find out the description of mathematics learning outcomes in fifth grade students of SD Al Hijrah Makassar after applying the Question Student Have learning model. 3) To find out the effectiveness of the application of the Question Student Have learning model in fifth grade students of SD Al Hijrah Makassar. The type of research applied by the author was the Pre-Experimental Design Research; this type did not include the true-experimental Design research. The form of research used was the One-Group Pretest- Posttest Design. The technique used by the author was saturated sampling, so the sample in this study was all fifth grade students of SD Al Hijrah Elementary Makassar, with total 31 students. Based on the results of descriptive analysis of data, it was found that the average acquisition of students 'cognitive scores before the application of the Question Student Have learning model was 39.87 and 61% of students from 31 students' mastery level of material were in the low category. While the average cognitive value of students after applying the Question Student Have learning model was 75.61 and 68% of students from 31 students mastering the material were in the high category. This showed an increased in the acquisition of the average value of students namely from 39.87 to 75.61. This meant that the Question Student Have learning model had effect very in improving student learning outcomes.Keywords: Question Student Have learning model, mathematics learning outcome.